2016
DOI: 10.1002/acr.22788
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐Year Retention Rate of First‐Line Tumor Necrosis Factor Inhibitors in Rheumatoid Arthritis: Real‐Life Data From a Local Registry

Abstract: Objective. To evaluate the 12-year survival of the first tumor necrosis factor inhibitor (TNFi) treatment in a cohort of rheumatoid arthritis (RA) patients, comparing the between-groups discontinuation rates for infliximab, etanercept, and adalimumab. Methods. RA patients treated with their first TNFi were investigated from a local registry. Before and after adjusting for propensity scores, overall and by individual TNFi 12-year drug retention was evaluated. Drug survival rates were calculated using the Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 28 publications
11
45
2
2
Order By: Relevance
“…Etanercept showed the highest persistence with treatment; at the end of the 4-year follow-up, the number of patients persisting with etanercept treatment was ~1.4 and 1.6 times higher than for infliximab and adalimumab, respectively. This finding is consistent with the results of two important Italian registries, GISEA (Italian Early Arthritis study)23 and LORHEN (Lombardy Rheumatology Network),24 and with another study that, based on a local registry, estimated persistence with therapy at 12 years of the three most commonly used TNF inhibitors for the treatment of RA, showing that the risk of discontinuation for adalimumab (hazard ratio [HR] 2.35 [95% CI 1.73–3.21]) and infliximab (HR 1.55 [95% CI 1.14–2.11]) was significantly greater than for etanercept 25…”
Section: Discussionmentioning
confidence: 89%
“…Etanercept showed the highest persistence with treatment; at the end of the 4-year follow-up, the number of patients persisting with etanercept treatment was ~1.4 and 1.6 times higher than for infliximab and adalimumab, respectively. This finding is consistent with the results of two important Italian registries, GISEA (Italian Early Arthritis study)23 and LORHEN (Lombardy Rheumatology Network),24 and with another study that, based on a local registry, estimated persistence with therapy at 12 years of the three most commonly used TNF inhibitors for the treatment of RA, showing that the risk of discontinuation for adalimumab (hazard ratio [HR] 2.35 [95% CI 1.73–3.21]) and infliximab (HR 1.55 [95% CI 1.14–2.11]) was significantly greater than for etanercept 25…”
Section: Discussionmentioning
confidence: 89%
“…In addition, drug profiles play an important role, with patients more likely to discontinue treatment due to a poor side-effect profile or lack of efficacy of a medication [23]. For example, in patients with rheumatoid arthritis, discontinuation rates due to inefficacy and adverse events were demonstrated in etanercept (17.5 and 22.4%, respectively), infliximab (44.1 and 36.7%, respectively) and adalimumab (50.4 and 31.2%, respectively) over a period of 12 years.…”
Section: Perception Of Biosimilars: Awareness and Communication Gapsmentioning
confidence: 99%
“…For example, in patients with rheumatoid arthritis, discontinuation rates due to inefficacy and adverse events were demonstrated in etanercept (17.5 and 22.4%, respectively), infliximab (44.1 and 36.7%, respectively) and adalimumab (50.4 and 31.2%, respectively) over a period of 12 years. These data highlight the importance efficacy and safety of a medication plays in patient adherence to treatment [23]. [14].…”
Section: Perception Of Biosimilars: Awareness and Communication Gapsmentioning
confidence: 99%
“…First-line biologic treatment survival in a population-based cohort was examined in a large Italian registry of patients with rheumatoid arthritis; the length of time examined (12 years) far exceeded prior attempts [32]. Examining survival for ETN, ADA, and IFX, the data revealed that the incidence of ETN withdrawal for secondary lack of efficacy was stable over 3 to 12 years whereas withdrawal for the mAbs progressively increased over the same period.…”
Section: Drug Survival Studiesmentioning
confidence: 99%